NEED ANALYSIS OF MATHEMATICS DIGITAL TEACHING MATERIAL - Safitri, Meilani; Aziz, M. Ridwan (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Today's mathematics learning paradigm has been transformed into digital-based learning. This research is a qualitative descriptive study. The purpose of this study is to describe the results of the needs analysis of digital mathematics teaching materials. Data were collected through questionnaires and interviews with 11 mathematics teachers in Ngemplak, Boyolali, Central Java. Data analysis in this study was carried out by qualitative analysis and descriptive analysis. The results of this study indicate that: 1) 9 teachers out of 11 teachers interviewed agreed that digital mathematics teaching materials need to be further developed, 2) based on the results of the questionnaire that we distributed to students, teachers, parents, principals, and school supervisors in Boyolali found that 76.5% of respondents wanted digital mathematics teaching materials to be developed.